2012
DOI: 10.1111/j.1466-7657.2012.01035.x
|View full text |Cite
|
Sign up to set email alerts
|

Job satisfaction among immigrant nurses in Israel and the United States of America

Abstract: Generalization of the findings is limited, because a convenience sample was used to recruit FSU and Filipino immigrant RNs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
17
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 26 publications
4
17
0
1
Order By: Relevance
“…However, this finding was similar to the results of a study on job satisfaction of Filipino RNs in the USA that reported a negative association between length of stay and lower levels of satisfaction with professional status, task requirements and organizational policies (Itzhaki et al. ). Possible reasons underlying this observation may be related to the lack of opportunities for career advancement and lack of recognition of overseas‐qualified nurses' previous nursing skills and knowledge.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…However, this finding was similar to the results of a study on job satisfaction of Filipino RNs in the USA that reported a negative association between length of stay and lower levels of satisfaction with professional status, task requirements and organizational policies (Itzhaki et al. ). Possible reasons underlying this observation may be related to the lack of opportunities for career advancement and lack of recognition of overseas‐qualified nurses' previous nursing skills and knowledge.…”
Section: Discussionsupporting
confidence: 89%
“…The finding that the longer overseas-qualified nurses remained in the host country, the less satisfied NESB nurses were with the work environment, was completely contrary to other studies that showed a positive correlation between length of stay and job satisfaction (Ea et al 2008;Xu et al 2008). However, this finding was similar to the results of a study on job satisfaction of Filipino RNs in the USA that reported a negative association between length of stay and lower levels of satisfaction with professional status, task requirements and organizational policies (Itzhaki et al 2013). Possible reasons underlying this observation may be related to the lack of opportunities for career advancement and lack of recognition of overseas-qualified nurses' previous nursing skills and knowledge.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…; Itzhaki et al. ). On the other hand, in a variety of past studies, autonomy and job satisfaction were dealt with as separate factors and the relationship between autonomy and job satisfaction was demonstrated (Carmel et al.…”
Section: Methodsmentioning
confidence: 98%